Permainan Tradisional sebagai Pengembangan Kecerdasan Emosi Anak - Lubis, Ramadhan; Khadijah, Khadijah (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2018)
Aspects of early childhood development include: Islamic religious education, social-emotional character and independence, language, cognitive, physical-motor and art. Early childhood requires concrete and interesting learning, as RA Al-Kamil and TKIT Nurul Ilmi applied traditional games. But not specifically analyzed the emotional development of children. Therefore, this study examined the emotional development of children using traditional games. The study was conducted in RA Al-Kamil and TKIT Nurul âIlmi in first semester of the Academic Year 2018/2019. Subjects in this study are teachers, principals, parents and children of group B. The instruments used were observation forms, interview guidelines and documentation. The research is qualitative. Data analysis techniques used were triangulation and validity. The results showed that (1)traditional games used were against marbles, long clogs, conklak and bakelan; and (2) the emotional development of children develops after the application of traditional games in RA.